Description of a new species of rabbitfish (Perciformes: Siganidae) from southern India, Sri Lanka and the Maldives - Woodland, David J.; Anderson, R. Charles (Zootaxa, 2014)
Siganus insomnis sp. nov. is described from the Maldives, Sri Lanka and southern India. It most closely resembles S. lineatus (Valenciennes) from the Western Pacific but differs in coloration, principally in that most if not all of the bronze bands on its mid and upper sides continue horizontally and unbroken through to the nape and opercular slit. By contrast, in S. lineatus, typically the anterior area below the spinous dorsal fin down to the mid-sides is irregularly marked with golden bronze spots, commas, or a maze of contorted lines. S. guttatus (Bloch) is the third member of this group of sibling species; its sides are covered with orange to bronze-gold spots. It is distributed throughout S.E. Asia, i.e., it occupies a geographic position between the areas inhabited by S. lineatus and S. insomnis. Thus the gene pools of S. lineatus and S. insomnis are quarantined from one another by distance and the intervening presence of S. guttatus in S.E. Asia. The geographical separation of the populations of S. lineatus and S. insomnis from one another is reinforced by the absence of suitable, coralline habitats for these species in the western half of the Bay of Bengal.